Neurological telerehabilitation in the COVID-19 era – current perspectives through a bibliometric analysis - Lebioda, Lúcia Aparecida; Pedroso, Bruno; Santos, Marlon Estevam Camilo dos; Pinto, Guilherme Moreira Caetano; Welling, Leonardo Christiaan (Frontiers in Neurology, 2023)
Objective To identify bibliometric parameters and research trends regarding to telerehabilitation of patients with stroke in the COVID-19 era. Methodology This is an integrative review carried out in the Scopus database, from June to July 2021, through the Biblioshiny graphical interface, provided by the Bibliometrix program. The search terms used were “Stroke,” “COVID-19” and “Telerehabilitation.” Results were filtered by publication date from 2019 onwards. No language restrictions were imposed. Results Twenty two articles were included in the study and the results were presented in the form of figures demonstrating that the journal Frontiers in Neurology was the one with the most relevant studies and the author with the highest number of citations. The Brazilian Academy of Neurology was the institution with the greatest number of studies and China ranked first as the country with the greatest scientific production. The authors used recent references in their work. A thematic map showed the centrality and density of the words presented and, finally, a three-field graph showed a strong intimacy between countries, keywords and authors. Conclusion A greater interest in the subject was observed in China with greater relevance of journals and institutions focused on neurology. However, despite telerehabilitation being an effective alternative in the context of the pandemic, few studies have explored this modality.